2003
DOI: 10.1016/s0248-4900(03)00087-x
|View full text |Cite
|
Sign up to set email alerts
|

Myosin heavy chain isoforms in postnatal muscle development of mice

Abstract: In this study, using a high-resolution gel electrophoresis technique, we have characterized the myosin heavy chain composition in different skeletal muscle of the mouse during postnatal development. The pattern of myosin heavy chain expression was studied in four hind limb muscles, the diaphragm, the tongue and the masseter. All of these muscles displayed the usual sequential transitions from embryonic to neonatal and to adult myosin heavy chain isoforms but more interestingly these transitions occur with a di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

25
223
1
11

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 230 publications
(260 citation statements)
references
References 51 publications
25
223
1
11
Order By: Relevance
“…2 We performed immunolabeling with anti-NCAM and anti-neonatal/perinatal/fetal MHC (MHCn), both of which are neurally and developmentally regulated. 1,11,12,20,21,25 The multigene family that encodes MHC is expressed in a developmentally regulated sequence. Developmental isoforms that have been characterized include MHCemb and MHCn.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…2 We performed immunolabeling with anti-NCAM and anti-neonatal/perinatal/fetal MHC (MHCn), both of which are neurally and developmentally regulated. 1,11,12,20,21,25 The multigene family that encodes MHC is expressed in a developmentally regulated sequence. Developmental isoforms that have been characterized include MHCemb and MHCn.…”
mentioning
confidence: 99%
“…Newly formed myofibers display a highly regulated, sequential transition from embryonic to neonatal and finally to adult myosin heavy chain isoforms. 1,20 The different forms of NCAM are a result of alternative splicing of a single gene and post-translational modifications. 9,18 NCAM is also upregulated in newly formed myofibers.…”
mentioning
confidence: 99%
“…Since it was first shown that the muscle fibers of mouse tongue consisted entirely of fast isoforms of MyHC (Dalrymple et al, 1999(Dalrymple et al, , 2000Shuler and Dalrymple, 2001), the composition ratio for each isoform has been studied in detail using gel electrophoresis (Agbulut et al, 2003). These studies have indicated that although MyHC-2b continues to increase after birth, MyHC-2a is expressed only transiently for several weeks postpartum.…”
Section: Discussionmentioning
confidence: 99%
“…Agbulut et al determined MyHC composition ratios in mouse tongue muscle and reported that while MyHC-2b increases from birth onward, MyHC-2a is expressed transiently, for only a few weeks postpartum (Agbulut et al, 2003). Moreover, tongue consists of both intrinsic and extrinsic muscles, and differences have been reported in the properties of fibers among the intrinsic muscles .…”
Section: Introductionmentioning
confidence: 99%
“…Mouse muscle is composed of four major fiber types, defined by their myosin heavy chain (MyHC) content as slow type I and fast type IIa, IIx, and IIb (Kelly and Rubinstein, 1994). To determine whether fiber type was a factor in the level of expression driven by A17, we examined the soleus muscle, because in mouse it contains approximately 50% slow type I and fast type IIa/IIx fibers (Agbulut et al, 2003). Immunostaining with MyHC-specific antibodies showed clearly that myonuclei with ␤-galactosidase activity were located in both fiber types (Fig.…”
Section: A17 Drives the Mrf4 Promoter In Both Fast And Slow Fiber Typesmentioning
confidence: 99%